Jigsaw Type Cooperative Learning Model to Improve Students' Cooperation and Tolerance Character at MI Siti Fatimah Tawangrejeni Turen - Hasanah, Uswatun; Chasanah, Uswatun; Talib, Uswatun Saidah A.; Zumirddat, Wa Ode (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the implementation of the Jigsaw Cooperative Learning model in improving the character of cooperation and tolerance of grade 5 students of MI Siti Fatimah, Tawangrejeni, Turen, Malang Regency. The Jigsaw model was chosen because it can encourage positive interactions between students through group-based learning, where each student is responsible for the part of the material that must be delivered to their group members. The research method used is classroom action research (CAR) with a qualitative and quantitative approach. Data were collected through observation, interviews, and questionnaires to students and teachers. The results showed that the implementation of the Jigsaw model significantly improved students' cooperation skills in completing group assignments and increased their tolerance towards differences of opinion. This can be seen from the increasing participation of students in discussions, attitudes of mutual respect, and the ability to resolve conflicts in a more constructive way. The Jigsaw Cooperative Learning model is effective in building students' character of cooperation and tolerance, which is very important in learning based on social values. This model is recommended for teachers to be applied in learning in order to create a more harmonious and collaborative classroom atmosphere.